Crystal structure of bis(2-{1-[(E)-(4-fluorobenzyl)imino]ethyl}phenolato-κ2N, O)palladium(II). (April 2015) - Tajuddin, Amalina Mohd; Bahron, Hadariah; Zaki, Hamizah Mohd; Kassim, Karimah; Chantrapromma, Suchada
No abstract available